Electrophophretic Variation in Feral Populations of Three Freshwater Species of Fish - Doyungan, Zaldy; Mencias, Claire; Isidro, Stephanie; Rosales, Ma. Theresa (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Analysis of hemoglobin and plasma esterase in the blood sample of three feral freshwater species of fish, namely, spotted gourami (Trichogaster trichoptenus), mudfish (Channa striata) and catfish (Clarias macrocephalus) was conducted using horizontal starch gel electrophoresis. Results revealed that both the hemoglobin (HB) and plasma esterase (EST) loci in T. tricoptenus showed polymorphism, consisting of two alleles as indicated by two codominant/y. Migrating anodal electromorphs. For C. striata, only the HB locus showed polymorphism being governed by two alleles while the EST locus showed monomorphic expression. Likewise, monomorphic expression was observed in both loci in the C. macrocephalus.